UPAYA PENINGKATAN HASIL BELAJAR BOLA VOLI MELALUI MODIFIKASI DYNAMIC WARM UP PERMAINAN TRADISIONAL BUGIS PADA SISWA KELAS XI SMA NEGERI 25 BONE - Lisnawati, Lisnawati; Maria Herlinda Dos Santos; Mutmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the implementation of a modified dynamic warm-up based on Bugis traditional games and its effectiveness in improving volleyball learning outcomes among eleventh-grade students of SMA Negeri 25 Bone. The study was motivated by the low enthusiasm of students during conventional warm-up activities, which affected their volleyball learning outcomes. Therefore, a dynamic warm-up integrated with Bugis traditional games was applied as an innovative, enjoyable, and meaningful learning strategy. This research employed Classroom Action Research (CAR) consisting of two cycles.